Identification and molecular characterization of zoonotic rickettsiae and other vector-borne pathogens infecting dogs in Mnisi, Bushbuckridge, Mpumalanga Province, South Africa - Matjila, P.T. (Paul Tshepo) (University of Pretoria, 2015)
Dissertation (MSc)--University of Pretoria, 2014.